2004
DOI: 10.1073/pnas.0404743101
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of luteinizing hormone β-subunit leads to hypogonadism, defects in gonadal steroidogenesis, and infertility

Abstract: Luteinizing hormone (LH) and follicle-stimulating hormone (FSH) act on gonadal cells to promote steroidogenesis and gametogenesis. Clarifying the in vivo roles of LH and FSH permits a feasible approach to contraception involving selective blockade of gonadotropin action. One way to address these physiologically important problems is to generate mice with an isolated LH deficiency and compare them with existing FSH loss-of-function mice. To model human reproductive disorders involving loss of LH function and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(232 citation statements)
references
References 49 publications
12
218
1
1
Order By: Relevance
“…LHβ KO phenotype has been recently reported (Ma et al, 2004). As expected, the phenotype closely resembles that of LHR KO mice, with infertility of both sexes, hypoplastic sex organ development and reduced androgen and estrogen levels.…”
Section: Lh/hcg-r Knockout (Lurko) Micesupporting
confidence: 70%
“…LHβ KO phenotype has been recently reported (Ma et al, 2004). As expected, the phenotype closely resembles that of LHR KO mice, with infertility of both sexes, hypoplastic sex organ development and reduced androgen and estrogen levels.…”
Section: Lh/hcg-r Knockout (Lurko) Micesupporting
confidence: 70%
“…Functional LHR in humal fetal Leydig cells is thus compulsory for their androgen synthesis, whereas in the mouse, as discussed above, paracrine or other endocrine factors must be able to maintain sufficient androgen synthesis by the fetal Leydig cells to induce masculinisation. The same species difference in fetal Leydig cell function is not, however, found in the case of LH inactivation (LofranoPorto et al, 2007;Valdes-Socin et al, 2004;Weiss et al, 1992;Ma et al, 2004)). In the human, placental hCG (an agonist of LH) can take over the function of missing LH while in the mouse, as we have shown, a number of different factors are able to compensate for missing LH.…”
Section: Post-natal Developmentmentioning
confidence: 90%
“…In the mouse and rat it is not, however, clear how fetal Leydig cell function is regulated. Postnatal Leydig cells are critically dependent on LH and fetal Leydig cells respond to LH in vitro but Leydig cell function is normal in the fetus in the absence of LH or its receptor (O'Shaughnessy et al, 1998;Zhang et al, 2001b;Ma et al, 2004).…”
Section: Fetal Leydig Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, genetic studies using mutant mouse models have identified defects in morphogenesis (Bomgardner et al, 2003;Kitagaki et al, 2011;Podlasek et al, 1999), development (Robaire, 2005;Tomaszewski et al, 2007;Yoshio et al, 2010), and function (Grover et al, 2005;Krishnamurthy et al, 2001;Krishnamurthy et al, 2000;Ma et al, 2004;Mendive et al, 2006) of the epididymis as a result of deletions engineered in various gene loci.…”
Section: Introductionmentioning
confidence: 99%